LOCAL EXPERIENCE OF TELEMEDICINE: EXAMPLES OF CASES IN YEMEN - Ishak, Abdulrahman A.; Alhadi, Abdulrahman M; Al-Shamahy, Hassan A. (Universal Journal of Pharmaceutical Research, 2021)
Background: The benefits of establishing a web-based telemedicine service in a resource-stressed society, linking health professionals in order to improve the quality and accessibility of healthcare and facilitate a further method of medical education through exchange of knowledge and experiences. Sub-standard communication facilities within a strained medical service across limited sites, combined with an inadequate understanding of the service further reduces provision. The on-going military campaign within the country exacerbates the problems facing medical staff, yet despite the difficult situation in the country there is a drive towards an increase in health facilities. Objective: The aim of this research is to explore one of the first experiences in the use of telemedicine in Yemen by clarifying cases that have benefited from telemedicine and further exploring the potential for development of a network of TM to serve areas which lack sub-specialty services. Methods: We carried out a review of both the first and second phases of our experience of TM services in Yemen. The first phase began in 1997 when we joined a newly established international company based in the USA with several offices in different countries. We got a huge, expensive digitizer that was supposed to transfer medical reports to second opinion sites in USA, UK, Jordan etc. The second phase began a few years later utilizing a free service, namely The Swinfen Charitable Trust, based in the UK; in which 300 cases in the first stage with 1-3 responses and about 80 cases with 5-50 responses and more in the second stage were involved and benefited from TM services. Results: During the study period the process was seen to be generally very useful to patients helping the local doctor to give the correct decision on management and treatment; added to that cases had reduced travel and the specialist advice proved educational for the doctors who received their guidance. Conclusion and recommendation: This study revealed that telemedicine services are generally underutilized in Yemen despite the good results achieved in many of the cases. Technical, administrative, and legal issues should be discussed in Yemen. Factors such as on-going problems with internet connectivity and consequent system reliability must also be considered. Knowing and identifying these factors is vital for considering any future in-depth studies and assessing the appropriate measures to fix the technological problems that face TM in Yemen are an on-going concern. Peer Review History: Received 11 December 2020; Revised 5 January 2021; Accepted 13 February; Available online 15 March 2021 Academic Editor: Essam Mohamed Eissa , Beni-Suef University, Egypt, dressamceutics@yahoo.com Reviewer(s) detail: Dr. George Zhu , Tehran University of Medical Sciences, Tehran, Iran, sansan4240732@163.com Dr. Evren Alğin Yapar , Turkish Medicines and Medical Devices Agency, Turkiye, evren.yapar@yahoo.com